Formulation and delivery of itraconazole to the brain using a nanolipid carrier system - Lim WM; Rajinikanth PS; Mallikarjun C; Kang YB (International Journal of Nanomedicine, 2014)
Wei Meng Lim,1 Paruvathanahalli Siddalingam Rajinikanth,2 Chitneni Mallikarjun,1 Yew Beng Kang11School of Pharmacy, International Medical University, Kuala Lumpur, Malaysia; 2School of Pharmacy, Taylor’s University, Selangor, MalaysiaAbstract: The objectives of this study were to develop and characterize itraconazole (ITZ)-loaded nanostructured lipid carriers (NLCs) and to study their potential for drug delivery into the brain. Precirol® ATO 5 and Transcutol® HP were selected as the lipid phase, and Tween® 80 and Solutol® HS15 as surfactants. The ITZ-NLCs were prepared by a hot and high-pressure homogenization method. The entrapment efficiency for the best formulation batch was analyzed using high-performance liquid chromatography and was found to be 70.5%±0.6%. The average size, zeta potential, and polydispersity index for the ITZ-NLCs used for animal studies were found to be 313.7±15.3 nm, –18.7±0.30 mV, and 0.562±0.070, respectively. Transmission electron microscopy confirmed that ITZ-NLCs were spherical in shape, with a size of less than 200 nm. Differential scanning calorimetry and X-ray diffractometry analysis showed that ITZ was encapsulated in the lipid matrix and present in the amorphous form. The in vitro release study showed that ITZ-NLCs achieved a sustained release, with cumulative release of 80.6%±5.3% up to 24 hours. An in vivo study showed that ITZ-NLCs could increase the ITZ concentration in the brain by almost twofold. These results suggest that ITZ-NLCs can be exploited as nanocarriers to achieve sustained release and brain-targeted delivery.Keywords: lipid nanoparticles, brain delivery, nanostructured lipid carrier